2021
DOI: 10.3847/1538-4357/ac18ce
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Interstellar Medium of Star-forming Galaxies, as Traced by Stardust*

Abstract: This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL above for details on accessing the published version.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 212 publications
3
30
0
Order By: Relevance
“…the COSMOS sample has higher fitted τ f B , indicating a higher average M dust , compared to SDSS and GAMA at similar M * , our results imply a correlation between the M dust -M * ratio and redshift, which is consistent with the literature (e.g., Liu et al 2019;Magnelli et al 2020;Kokorev et al 2021).…”
Section: Evolution Of Dust Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…the COSMOS sample has higher fitted τ f B , indicating a higher average M dust , compared to SDSS and GAMA at similar M * , our results imply a correlation between the M dust -M * ratio and redshift, which is consistent with the literature (e.g., Liu et al 2019;Magnelli et al 2020;Kokorev et al 2021).…”
Section: Evolution Of Dust Propertiessupporting
confidence: 91%
“…We compare the fitted values for r bulge to the average and 32-68th percentile of the bulge-to-total distribution of the selected samples, labeled as data. galaxies with higher M * have higher M dust (e.g., Liu et al 2019;Magnelli et al 2020;Kokorev et al 2021) hinting at the paired production of stars and dust (e.g., De Vis et al 2017;Pastrav 2020). The correlation with µ * is similar to the Grootes et al (2013) relation for low-z galaxies but deviates for high-µ * galaxies and high-z because the T04 model is unable to cover the high τ B estimated by the Grootes et al (2013) relation for these bins.…”
Section: Dependence Of Model Parameters On Galaxy Propertiesmentioning
confidence: 99%
“…For the galaxies with a Herschel counterpart (69/88) we employed the panchromatic SED fitting tool Stardust 2 developed by Kokorev et al (2021). In summary, this code performs a multi-component fit that combines linearly stellar libraries, AGN torus templates, and IR models of dust emission from star formation.…”
Section: Infrared Sed Fittingmentioning
confidence: 99%
“…Investigation of the evolution of the cold gas density has uncovered that it closely follows the evolution of the SFR density (e.g., Riechers et al 2019;Decarli et al 2019;Magnelli et al 2020). In the last decade, numerous studies have progressively revealed the increase in the gas content and decrease in the depletion timescales with increasing redshift (e.g., Daddi et al 2008Daddi et al , 2010Tacconi et al 2010;Genzel et al 2010;Magdis et al 2012;Béthermin et al 2015;Dessauges-Zavadsky et al 2020;Donevski et al 2020;Kokorev et al 2021). More recently, large statistical galaxy samples have established the gas scaling relations for the gas fractions ( f gas = M gas /(M gas + M * )) and depletion timescales (τ dep = M gas /SFR), with their dependencies on a specific star formation rate (sSFR = SFR/M * ), stellar mass, as well as lookback time (e.g., Scoville et al 2017;Tacconi et al 2018;Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We fit the available photometry from UV to mm wavelengths with the SED-fitting code STARDUST 108 , which models the emission from stars, active galactic nucleus (AGN), and infrared emission arising from dust heated by star formation. The method does not rely on energy balance assumptions, and rather fits an independent linear combination of templates.…”
Section: Uv-millimeter Sed Fittingmentioning
confidence: 99%